Human Papillomavirus (HPV) Prevalence in Nasal and Antrochoanal Polyps and Association with Clinical Data - Knör, Mareike; Tziridis, Konstantin; Agaimy, Abbas; Zenk, Johannes; Wendler, Olaf (PLoS ONE, 2015)
The pathogenesis of sinonasal polyposis remains unclear, in spite of several investigative approaches. Antrochoanal polyps, a subgroup of sinonasal polyposis along with allergic- and chronic-inflammatory nasal polyps, mostly originate from the maxillary sinus and develop as a unilateral, pedunculated mass towards the nasopharynx. The human papillomavirus (HPV) is discussed as a possible causative and influencing factor in development and progression of sinonasal polyposis. This study aims to elucidate HPV frequency in nasal polyps and antrochoanal polyps.Genomic DNA from 257 tissue specimens (166 nasal polyps, 39 antrochoanal polyps and 52 nasal turbinates) was subjected to three different established HPV- polymerase chain reaction assays, testing for 37 low- and high-risk HPV. In addition, immunohistochemical analyses for HPV16 were carried out, as well as immunohistochemistry and western blots of p16, a biomarker for HPV induced cancer.HPV-DNA was detected in 53.8% of antrochoanal polyps, 15.1% of nasal polyps, and 5.8% of nasal turbinates. HPV16 was the predominant type with a detection rate of 76% in nasal polyps and 62% in antrochoanal polyps. Immunohistochemically, HPV positive tissues stained positive for HPV16 antigens and p16 in epithelial cell layers. No significant p16 overexpression was traceable in antrochoanal polyps, nasal polyps and nasal turbinates by western blot. There was no correlation of HPV-status with sex, age, smoking, alcohol consumption or allergic background.The present study shows a significant frequency of high-risk type HPV16 in antrochoanal polyps. Absence of oncogenic transformation or correlation of the HPV-status with clinical data suggests a latent superinfection, possibly because of anatomical proximity to the oropharynx.
EVALuna2:6739